A method for identifying the learning curve for the surgical stabilization of rib fractures. Issue 6 (19th December 2022) - Delman, Aaron M.; Turner, Kevin M.; Ammann, Allison M.; Millar, D A.; Goodman, Michael D.; Janowak, Christopher F.
Abstract : Rib plating is increasingly commonly used for severe chest wall injuries, yet little is known about the development of operative competency. Here the use of cumulative sum (CUSUM) analysis is employed to elucidate the learning curve of rib plating. Abstract : BACKGROUND: Surgical stabilization of rib fractures (SSRF) is an accepted efficacious treatment modality for patients with severe chest wall injuries. Despite increased adoption of SSRF, surgical learning curves are unknown. We hypothesized intraoperative duration could define individual SSRF learning curves. METHODS: Consecutive SSRF operations between January 2017 and December 2021 at a single institution were reviewed. Operative time, as measured from incision until skin closure, was evaluated by cumulative sum methodology using a range of acceptable "missteps" to determine the learning curves. Misstep was defined by extrapolation of accumulated operative time data. RESULTS: Eighty-three patients underwent SSRF by three surgeons during this retrospective review. Average operative times ranged from 135 minutes for two plates to 247 minutes for seven plates. Using polynomial regression of average operative times, 75 minutes for general procedural requirements plus 35 minutes per plate were derived as the anticipated operative times per procedure. Cumulative sum analyses using 5%, 10%, 15%, and 20% incident rates for not meeting expected operative times, or "missteps" were used. An institutional learning curve between 15 and 55 SSRF operations was identified assuming a 90% performance rate. An individual learning curve of 15 to 20 operations assuming a 90% performance rate was observed. After this period, operative times stabilized or decreased for surgeons A, B, and C. CONCLUSION: The institutional and individual surgeon learning curves for SSRF appears to steadily improve after 15 to 20 operations using operative time as a surrogate for performance. The implementation of SSRF programs by trauma/acute care surgeons is feasible with an attainable learning curve. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level IV. Abstract :